Health challenges related to bereavement : –widows and widower’s experiences - Holm, Anne Lise; Berland, Astrid Karin Elde (Nordisk Tidsskrift for Helseforskning, 2024)
Grief is defined as a break in ties to the deceased, adjustment to new life conditions, in addition to problems with building new relationships. The aim of the study was to explore what experiences widows and widowers have with various health challenges related to grief and loss, and what was experienced as helpful? The study used an explorative design and qualitative method. The main theme was: "Need for self-determination". Det first theme revealed that the widows and widowers would rather manage on their own and not bother others with their physical health problems. The second theme revealed that they used withdrawal as a survival strategy. The third theme showed that contact with others provides health benefits. Bereavement do not have any limit in time and mourning can be a lifelong experience for elderly widows and widower. Social aspects had impact on what was perceived as helpful.